Fisibilitas Finansial Pengendalian Traktor Tangan dengan Sistem Android Berbasis Jaringan WiFi di Agroindustri Lahan Basah - Handoko, Widi; Rejo, Amin; Panggabean, Tamaria (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Handoko, W., Rejo, A., & Panggabean, T. (2024). Financial feasibility assessment of hand tractor controlled by android system wifi network based in wetland agroindustry. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 895–905). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The advancement of agricultural practices in Indonesia, particularly in wetland tillage, through the introduction of Android-controlled hand tractors is essential to tackle the challenges posed by diminishing labor and agricultural land. This study aimed to evaluate the financial viability of implementing a Wi-Fi-based Android-controlled hand tractor in comparison to manual operation. The methodology encompasses technical field capacity testing, cost efficiency, and financial assessment. The financial analysis of the five-year investment simulation revealed a Net Present Value (NPV) of IDR 19,918,961, an Internal Rate of Return (IRR) of 28.03%, a payback period of 1.78 years, and an ROI of 60.15%, which is 10.4% lower than the conventional method. These findings suggest that investing in this technology is not only financially feasible but also profitable. The adoption of Android-controlled hand tractors enhances productivity and has the potential to yield substantial economic returns for the agricultural sector.